Anthracene-Pentacene Dyads: Synthesis and OFET Characterization - Hauschild, Miriam; Chen, Lan; Etschel, Sebastian; Ferguson, Michael J.; Hampel, Frank; Halik, Marcus; Tykwinski, Rik R. (ChemPlusChem, 2020)
The synthesis of a series of unsymmetrical derivatives of pentacene appended with functionalized anthracene moieties is reported. These anthracene-pentacene dyads have been characterized by UV-vis spectroscopy and cyclic voltammetry to examine their electronic properties. X-ray crystallographic analysis was used to examine the solid-state features of anthracene-pentacene dyads 1 a-d with H-, F-, Cl-, and Br- substituents on the 9-position of anthracene, and shows that the packing arrangement of anthracene-pentacene derivatives 1 b,d,e are remarkably similar irrespective of the presence of fluoride, bromide or methyl substituents. The pentacene-anthracene dyads have been incorporated into OTFTs to evaluate their semiconducting properties. The pentacene derivative 1 b shows ambipolar behavior using AlOx C14 PA as the gate dielectric (electron and hole mobilities of 7.6 ⋅ 10-3 and 1.6 ⋅ 10-1 cm2 V-1 s-1 ), while performance of all derivatives was poor using p-doped Silicon as the substrate. These studies highlight the importance of thin-film formation over molecular structure.
CRIS-Team Scopus Importer:2020-05-22
Keywords: acenes; anthracenes; organic field-effect transistor; organic semiconductor; pentacenes